Snakes and Souks: Zoonotic pathogens associated to reptiles in the Marrakech markets, Morocco - Mendoza-Roldan, Jairo Alfonso; Noll Louzada-Flores, Viviane; Lekouch, Nouha; Khouchfi, Intissar; Annoscia, Giada; Zatelli, Andrea; Beugnet, Frédéric; Walochnik, Julia; Otranto, Domenico (PLoS neglected tropical diseases, 2023)
The world-famous markets of Marrakech, also known in Arabic as souks, harbor a vast diversity of reptiles that are sold for medicinal/magic/pet purposes or used for snake charming. This unique epidemiological context has never been studied considering the interactions of humans, reptiles, and zoonotic pathogens. Thus, the aim of this study was to identify the parasites and pathogens present in blood and feces associated with handled reptiles in the markets of Marrakech to assess the risk of zoonotic transmission within the reptile-human interface. Privately owned reptiles ( n = 118), coming from vendors or snake charmers, were examined and blood and feces sampled. DNA was extracted and molecular screening (cPCR, nPCR, qPCR, dqPCR) was performed aiming to identify potentially zoonotic pathogens (i.e., Anaplasma / Ehrlichia spp., Rickettsia spp., Borrelia burgdorferi sensu lato, Coxiella burnetii , Babesia/Theileria spp., Cryptosporidium spp., Giardia spp., Leishmania spp., Cestoda). Overall, 28.9% (34/118) of reptiles were positive for at least one pathogen. In blood, Anaplasma spp. were detected in four snakes, with two Montpellier snakes positive for Anaplasma phagocytophilum , while Rickettsia spp. were detected in one Mediterranean chameleon and four puff adders. Leishmania tarentolae was molecularly detected in a Mediterranean chameleon and a Montpellier snake. In feces, the cox 1 gene generated a myriad of sequences for nematodes, cestodes, fungi and bacteria. Importantly, Proteus vulgaris was identified from a Mediterranean chameleon. Cryptosporidium spp. nPCR yielded a positive sample (i.e., Cryptosporidium sp. apodemus genotype I) from a Moroccan worm lizard, as well as for bacteria such as Pseudomonas aeruginosa in an Egyptian cobra, and Morganella morganii from a puff adder. Results from this study demonstrated the risk of zoonotic transmission of microorganisms and parasites present in blood and feces from reptiles that are brought to the souks in Marrakech, Morocco, to be sold for medicinal purposes or used for snake charming, being in direct and straight contact with humans.